P–289 Progesterone receptor is not downregulated in endometrial epithelial compartment during embryo receptivity phase in assisted reproductive cycles. (6th August 2021) - Palomino, W; Rivas, M P; Argandoña, F; Devoto, L; Fuenets, A; Muñoz, A; Gabler, F; Savaris, R; Lessey, B; Johnson, C
Abstract: Study question: Is progesterone receptor (PGR) downregulation disrupted within endometrial epithelial compartment, during embryo receptivity phase in assisted reproductive technology (ART) cycles? Summary answer: PGR is not downregulated in endometrial epithelial cells from ART cycles during embryo receptivity phase. What is known already: Progesterone (P4) promotes the downregulation of its own progesterone receptor (PGR). During the mid-luteal phase, PGR is downregulated in endometrial epithelial cells (EEC), a critical process for embryo implantation. Embryos are unable to attach to the maternal surface when PGR expression is sustained in EEC. Non-physiologic ovarian steroid produced or employed in ART cycles may alter endometrial development compromising its receptivity. Scarce information is available whether PGR is downregulated in EEC from ARTs including ovarian stimulation for in vitro fertilization (IVF) cycles or hormonal endometrial preparation for frozen thawed embryo transfer (HEP-FET). Study design, size, duration: Cross sectional study including endometrial samples from fertile women during natural cycle (FNC, n = 23), from infertile women submitted to IVF (n = 19) and from infertile women who underwent mock HEP-FET (n = 35). Samples were obtained between 2018–2019. Sample size was calculated considering a power of 90%, alpha error=0.05, an expected PGR expression of 2 and 0.5 in ART and FNC groups, respectively, having a standard deviation=0.9. At least 9 patients would be necessary in each group. Participants/materials, setting, methods: Endometrial samples were obtained during mid-luteal phase scheduled 7 days after ovulation in FNC, 5 days after oocyte retrieval in IVF without embryo transfer or 5 days after P4 supplementation in HEP-FET. Immunohistochemistry was employed to quantify PGR using histologic score (Hscore). PGR mRNA levels were determined by qRT-PCR from EEC dissected by laser capture microdissection. Anova test was used for comparing means of Hscore and mRNA among groups. Statistical significance was established as P < 0.05. Main results and the role of chance: No statistical differences were found in demographic characteristics including age, body mass index or endometrial thickness. The PGR expression was reduced in FNC compared to IVF and HP-FET endometria (0.6 ± 0.1, 1.9 ± 0.9 and 2.2 ± 0.9 respectively; P < 0.0001). The PGR mRNA levels from ECC dissected by laser capture microdissection were higher in IVF and HP-ET cycles compared to FNC (10.6 ± 3.1, 13.6 ± 2.3 and 0.8 ± 0.1 respectively; P < 0.0001) corroborating the elevated PGR Hscore in EEC from ART cycles. Limitations, reasons for caution: This is a descriptive study reporting failure of PGR downregulation in endometria from ART cycles with vaginal P4 supplementation during the luteal-phase. Whether interference or resistance to P4 signal is the mechanism involved in the failure of PGR down regulation in ART cycles needs to be determined Wider implications of the findings: PGR downregulation within EEC was shown in FNC. The retained PGR expression detected in most ART cycles may interfere with embryo implantation and might explain the restricted pregnancy success. Future studies might reveal whether PGR evaluation in EEC can predict embryo implantation. Trial registration number: Not Aplicable